(3CdMGf GdShGLY Hjf GdHGOj hGdeQGLYs - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdHGOi CejQ s
(3GdfSNI GdNGeSIs
(3LeY ajg eGhQO Hjfg hHjf aVdGA YUQg hGdCFeI GdPjf jLH Cf JcJH eMGSfge hQJH GdCSeGA ajg Ydi MQha GdeYLes
(3HBNQgG HNW UdGM GdOjf Hf YHOGddg Hf CMeO Hf TeS GdOjf Hf CejQ GdeDefjf GdegOi Hf jMji Gdjefi SfI (B1030 (3g` eG jajO bQGAJgG hGdGfJaGY HgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B114 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B352s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B21 - (3U (B426 s
Keywords: (3GdCOHs